SOD2 Cell Guard from Free Radicals in Humans and Fruit Flies - Rukiyani, Sri Tati (International Journal of Ecophysiology, 2025)
Superoxide dismutase 2 (SOD2) gene encodes the enzyme manganese superoxide dismutase (Mn-SOD) which plays a critical role in maintaining cellular redox homeostasis by dismuting superoxide radicals into hydrogen peroxide and oxygen. Localized in mitochondria, this enzyme protects mitochondrial DNA from oxidative damage caused by Reactive Oxygen Species (ROS), which can trigger mutations and carcinogenesis. The expression and activity of antioxidant enzymes such as SOD, catalase, and glutathione peroxidase are critical for ROS detoxification and genome stability. The human SOD2 gene, located on chromosome 6q25.3, consists of five exons and four introns, and encodes a homo-tetrameric protein with Mn³⁺ cofactor. Genetic variations, such as Val9Ala and Val16Ala polymorphisms, affect the structure of the mitochondrial targeting sequence and potentially increase susceptibility to various diseases. The SOD2 protein structure includes two functional domains containing residues essential for enzymatic activity, allowing the enzyme to perform its function in cellular defense against oxidative stress. Keywords: SOD2 , Mn-SOD, Reactive Oxygen Species , Mitochondria